THE INFLUENCE OF THE ROMANIAN LANGUAGE ON THE ROMANI IDIOM OF TURDA, ROMANIA - Yusuke SUMI (Diversitate si Identitate Culturala in Europa)
As is known, with any type of linguistic contact, interferences occur mo stly in the lexical field, the most penetrable and mobile part of the system of a language, the behaviour which is most subject to extralinguistic influences of historical, social, political economic nature. It is the field which best highlights bilateral influences – not only at the mere lexical - semantic level (loan, translation, linguistic ones), but also at the lexico - grammatical level (taking over of affixal elements, composition structures, changes of the grammatical class, conversion, with the related semantic implications). The issues that emerge in the case of the Romani language derive from the long - lasting diachronic nature of these interferences and from the multitude of influence sources. It is often possible that a language element should have entered the Romani speech through other language. On the other hand, their almost exclusively oral circulation makes it much more difficult to identify the origin of some words which are in a long process of successive adoptions at the phono - morphological and semantic level.